The Influence of Chewing Habits on the Degree of Impacted Cerumen - Asti Widuri (Universitas Muhammadiyah Yogyakarta, 2021)
Abstract: Cerumen was glandular secretions at the outer one-third of the ear mixed with exfoliated squamous epithelium. The jaw's movement keeps the cerumen in the ear canal in a state of balance, so it is clean, protects and lubricates the external auditory canal. Impacted cerumen is also caused by excessive production, narrow canal anatomy, viscosity wax, and irritation due to cotton-tipped swabs habits. This study aims to determine whether chewing habits influence the degree of cerumen obstruction in patients with impacted cerumen. The study was a cross-sectional method in impacted cerumen patients at 17-80 years old in the ENT clinic of District Hospital Wates, Kulon Progo, Yogyakarta, Indonesia. Risk factors assessed were education, age, gender, chewing habits, and cotton-tipped swabs habits. The data were then analyzed by chi-square test. Of 80 respondents with the dominant age range 17-38 years (58.8 %), the number of males was 47 (58.8 %), and females were 33 (41.2 %). The significant risk factors comprised the chewing habit and the use of cotton-tipped swabs. Factors affecting the degree of cerumen in patients with impacted cerumen were the chewing habits and cotton-tipped swabs habits.